Solid Substrate Fermentation of Mycoherbicidal Agent Alternaria alternata FGCC#25 - Dipankar Majumdar2, Adarsh Pandey3 and A. K. Pandey, Jaya Singh1* (Recent Research in Science and Technology, 2010)
Optimization of suitable fermentation technology for mass production of mycoherbicides is the main aim of the present study and selection of suitable cheaper and easily available agro-waste substrate for the mass production of mycoherbicidal agent. Alternaria alternata FGCC#25 which is highly effective bionerbicidal agent against Lantana camara L is the main objective of this study. The out come of the study indicates that host leaf was most suitable solid substrate for the mass production of the mycoherbicidal agent Alternaria alternata FGCC#25 (1.36 x 108 spores/gm) for the effective managements of the weed Lantana camara L.